Study of cognitive and affected trust in knowledge sharing evidence from Chinese firms – A review paper. Issue 1 (2nd January 2019) - Zhang, Xiao Juan; Khan, Farhan; Jinpeng, Xiang; Khan, Kashif Ullah
Abstract : In the view of Social Exchange Theory (SET), this article provides an insight into the knowledge sharing behavior of an employee in the organization. Trust is a core factor affecting knowledge sharing behavior. To examine knowledge sharing behavior, it is needed to explore the employee's behavior towards sharing information. In this study we examine knowledge sharing behavior in those organization which are using information and communication technologies (ICTs) in their daily routine. We found that when employees trust each other, they tend to share more information. Results confirm that trust among employees influences the higher rate of knowledge sharing.